Respostas
respondido por:
1
(3²)^x = _1_
27
3^(2x) = 3^(-3)
então
2x = -3
x = - 3/2
V = {-3/2}
27
3^(2x) = 3^(-3)
então
2x = -3
x = - 3/2
V = {-3/2}
respondido por:
1
27 = 3³
1/27 = 3⁻³
9 = 3²
Portanto
9ˣ = 1/27
3²ˣ = 3⁻³
Como as bases são iguais, igualamos os expoentes:
2x = -3
x = -3/2
=)
1/27 = 3⁻³
9 = 3²
Portanto
9ˣ = 1/27
3²ˣ = 3⁻³
Como as bases são iguais, igualamos os expoentes:
2x = -3
x = -3/2
=)
Perguntas similares
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás